A 7000‐year history of changing plant trait composition in an Amazonian landscape; the role of humans and climate. (18th March 2019) - van der Sande, Masha T.; Gosling, William; Correa‐Metrio, Alexander; Prado‐Junior, Jamir; Poorter, Lourens; Oliveira, Rafael S.; Mazzei, Lucas; Bush, Mark B.
Abstract: Tropical forests are shifting in species and trait composition, but the main underlying causes remain unclear because of the short temporal scales of most studies. Here, we develop a novel approach by linking functional trait data with 7000 years of forest dynamics from a fossil pollen record of Lake Sauce in the Peruvian Amazon. We evaluate how climate and human disturbances affect community trait composition. We found weak relationships between environmental conditions and traits at the taxon level, but strong effects for community‐mean traits. Overall, community‐mean traits were more responsive to human disturbances than to climate change; human‐induced erosion increased the dominance of dense‐wooded, non‐zoochorous species with compound leaves, and human‐induced fire increased the dominance of tall, zoochorous taxa with large seeds and simple leaves. This information can help to enhance our understanding of forest responses to past environmental changes, and improve predictions of future changes in tropical forest composition.